Bridging multiple worlds : cultures, identities, and pathways to college - Cooper, Catherine R. (Oxford : Oxford University Press, 2011)
Considering research, practice, and policies on opening pathways to overcome educational disparities, this book offers new quantitative and qualitative evidence to introduce a multi-level theory on how youth navigate across the cultural worlds of their families, schools, peers, and community programs to access academic opportunities.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Keywords: Students with social disabilities -- Education -- United States; Educational equalization -- United States